THE EFFECT OF MIND MAPPING STRATEGY ON READING COMPREHENSION OF NARRATIVE TEXTS OF THE SECOND YEAR STUDENTS OF SMPN 13 PEKANBARU - Sari, Suci Kuspita; Azhar, Fadly; Ras, Fakhri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This pre-experimental research was aimed at finding out whether there is a significant effect of MindMappingstrategy on reading comprehension of narrative texts of the second year students of SMPN 13 Pekanbaru. Theresearch model was one group pretest-posttest design. The population were the second year students in academic year 2016/2017. The sample size was 40 students out of the population, chosen by using cluster sampling technique. The needed data were collected by administering a reading comprehension test of narrative texts in pre-test and post-test. The collected data were analyzed by using SPSS version 16.0. The finding of the research showed that the mean score of post-test was higher than that of pre-test (71.50>63.88). The value of t-test was higher than t-table (9.03>2.02) at 5% of the significance level. Therefore, alternative hypothesis (Ha) was accepted. It means that mind mapping strategy was effective for teaching reading comprehension in narrative texts. The implication of the finding was that the use of mind mapping strategy is a meaningful one in the part of the students in increasing the level of reading comprehension.Key Words: Mind Mapping, Reading Comprehension, Narrative Texts.